Functions: \(f\), \(g\), \(y\), \(u\), \(v\)

Argument (independent variable): \(x\)

Argument (independent variable): \(x\)

Real constant: \(k\)

Angle: \(\alpha\)

Angle: \(\alpha\)

- The derivative of a function \(y = f\left( x \right)\) measures the rate of change of \(y\) with respect to \(x\). Suppose that at some point \(x \in \mathbb{R}\), the argument of a continuous real function \(y = f\left( x \right)\) has an increment \(\Delta x\). Then the increment of the function is equal to

\(\Delta y = f\left( {x + \Delta x} \right) \,-\) \(f\left( x \right).\)

The derivative of the function \(y = f\left( x \right)\) at the point \(x\) is defined as the limit of the ratio \(\Delta y/\Delta x\) as \(\Delta x \to 0:\)

\(y’ = f’\left( x \right) = {\large\frac{{dy}}{{dx}}\normalsize} =\) \({\large\frac{{df\left( x \right)}}{{dx}}\normalsize} =\) \(\lim\limits_{x \to 0} {\large\frac{{\Delta y}}{{\Delta x}}\normalsize} =\) \(\lim\limits_{x \to 0} {\large\frac{{f\left( {x + \Delta x} \right) – f\left( x \right)}}{{\Delta x}}\normalsize}.\) - From a geometrical point of view, the derivative of a function \(y = f\left( x \right)\) at a point \(x\) is equal to the slope of the tangent line to the curve \(f\left( x \right)\) drawn through this point:

\({\large\frac{{dy}}{{dx}}\normalsize} = \tan \alpha \) - The derivative of the sum of two functions is equal to the sum of their derivatives:

\({\large\frac{{d\left( {u + v} \right)}}{{dx}}\normalsize} = {\large\frac{{du}}{{dx}}\normalsize} + {\large\frac{{dv}}{{dx}}\normalsize}\) - The derivative of the difference of two functions is equal to the difference of their derivatives:

\({\large\frac{{d\left( {u – v} \right)}}{{dx}}\normalsize} = {\large\frac{{du}}{{dx}}\normalsize} – {\large\frac{{dv}}{{dx}}\normalsize}\) - A constant factor can be taken out of a derivative:

\({\large\frac{{d\left( {ku} \right)}}{{dx}}\normalsize} = k{\large\frac{{du}}{{dx}}\normalsize}\) - Derivative of the product of two functions

\({\large\frac{{d\left( {u \cdot v} \right)}}{{dx}}\normalsize} =\) \( {\large\frac{{du}}{{dx}}\normalsize} \cdot v + u \cdot {\large\frac{{dv}}{{dx}}\normalsize}\) - Derivative of the quotient of two functions

\({\large\frac{d}{{dx}}\normalsize}\left( {{\large\frac{u}{v}}\normalsize} \right) =\) \({\large\frac{{\frac{{du}}{{dx}} \cdot v – u \cdot \frac{{dv}}{{dx}}}}{{{v^2}}}\normalsize}\) - Derivative of a composite function (chain rule)

\(y = f\left( {g\left( x \right)} \right),\) \(u = g\left( x \right),\) \({\large\frac{{dy}}{{dx}}\normalsize} = {\large\frac{{dy}}{{du}}\normalsize} \cdot {\large\frac{{du}}{{dx}}\normalsize}\) - Derivative of an inverse function

\({\large\frac{{dy}}{{dx}}\normalsize} = {\large\frac{1}{{dx/dy}}\normalsize},\)

where \(x\left( y \right)\) is the inverse function for \(y\left( x \right).\) - \({\large\frac{d}{{dx}}\normalsize} \left( {{\large\frac{1}{y}}\normalsize} \right) =\) \( – {\large\frac{{dy/dx}}{{{y^2}}}\normalsize}\)
- Logarithmic derivative

\(y = f\left( x \right),\) \(\ln y = \ln f\left( x \right),\) \({\large\frac{{dy}}{{dx}}\normalsize} =\) \(f\left( x \right) \cdot {\large\frac{d}{{dx}}\normalsize} \left[ {\ln f\left( x \right)} \right]\)